Effect of Ashwagandha (Withania somnifera) on cardiac aquaporins in adolescent rats under a chronic unpredictable mild stress model - Baksi, N.; Gokdemir, G.Ş.; Arkaş Alklay, A.; Karakoç, Z. (Polish Journal of Veterinary Sciences, 2026)
Adolescent depression is a prevalent and serious mental health issue that can negatively impact multiple organ systems, including the cardiovascular system. This study investigates the effects of chronic unpredictable mild stress (CUMS), a validated animal model of depression, on the expression of Aquaporins (AQP1, AQP2 and AQP3) in the cardiac tissue of adolescent rats and evaluates the potential therapeutic role of ashwagandha (Withania somnifera (L.) Dunal). Twenty-eight male Wistar albino rats were divided into four groups: Control, CUMS, CUMS+SERT, and CUMS+ASHW. Treatments were administered via oral gavage for 28 days, and cardiac tissues were evaluated histologically, immunohistochemically and biochemically. While serum levels of CK, Na, Cl and K showed no significant differences across groups, histological examination revealed myocardial damage (edema, hemorrhage, vacuolization) in CUMS rats. Immunohistochemical analysis demonstrated strong AQP1 expression across all groups, while AQP2 and AQP3 showed increased expression in treatment groups compared to the control. These findings suggest that Ashwagandha may mitigate stress-induced cardiac changes and influence aquaporin expression, particularly AQP2 and AQP3, which could be relevant to cardiac water balance and function in depression. Further studies are warranted to explore the molecular mechanisms linking aquaporin modulation and cardioprotection in stress-related pathologies.